2015
DOI: 10.31018/jans.v7i2.680
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thiamethoxam 70% WS as seed treatment against early sucking pests of tomato

Abstract: The present investigation was carried out at Vegetable Research Centre, G. B. Pant University of Agriculture and Technology, Pantnagar, Uttarakhand during the 2013 and 2014 to evaluate the effectiveness of thiamethoxam, used as seed treatment against the sucking insects of tomato. The seed treatment with thiamethoxam protected tomato seedlings from aphids and thrips at the early season from the onset of seed planting. There was a fast initial effect against the pests then gradually decreased to reach a moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The obtained results are in agreement with Maurya et al (2015) who reported that the highest tomato yield was recorded by thiamethoxam 70%WS at rate of 4.2 g a.i./kg of seed followed by the rate of 3.85 g a.i./kg of seed as compared to untreated.…”
Section: Effect Of Imidacloprid On Fruit Yield Of Tomatosupporting
confidence: 92%
See 1 more Smart Citation
“…The obtained results are in agreement with Maurya et al (2015) who reported that the highest tomato yield was recorded by thiamethoxam 70%WS at rate of 4.2 g a.i./kg of seed followed by the rate of 3.85 g a.i./kg of seed as compared to untreated.…”
Section: Effect Of Imidacloprid On Fruit Yield Of Tomatosupporting
confidence: 92%
“…Moreover, El-Naggar and Zidan (2013) reported that cotton seedlings protected from thrips infestation for at least 6 weeks from seed planting by seed treatment with imidacloprid and thiamethoxam, and induced a fast initial effect on whitefly stages. Recently, Maurya et al (2015) found that thiamethoxam can protect tomato seedlings from the infestation with aphids and thrips when it treated as seed treatment, and Somasundar et al (2016) assessed the influence of seed treatment on insect pests in green gram and found that thiamethoxam at 4.3 g/kg and 8.6 g/kg was greatly effective against sucking piercing insects as aphids, thrips, leaf hoppers, where the leaf damage was decreased in thiamethoxam, imidacloprid, acetamiprid treatments. Smith and Giurcanu (2013) reported that egg and nymph densities were significantly lower on tomato seedling treated with insecticides than untreated control, whether whitefly adults were introduced 3, 7 or 14 days after the insecticides on treated plants tended to be very low.…”
Section: Resultsmentioning
confidence: 99%
“…These results confirm the results of the previous season. The present findings are in line with those of Maurya et al (2015), who discovered that the application of several insecticides markedly raised aphid mortality. Effects the tested insecticides against the predators in potato field:…”
Section: Efficacy Of the Tested Insecticides Against A Gossypii In Po...supporting
confidence: 93%
“…The obtained results are in agreement with Naveed et al (2010) who reported that cotton seed treated with thiamethoxam kept the population of B. tabaci below the economic threshold level (6 leaf -1 ) up to 50 days after sowing seed compared with the control. Also, Maurya et al (2015) found that tomato seed treated with Thiamethoxam 70% WS at 4.2 g a.i /kg of seed reduced the early season insect pests (aphids and thrips) as well as significantly increased the fruit yield. Recently, Ding et al (2018) treated successfully corn seeds with thiamethoxam against early-season thrips and reduced yield losses under field conditions.…”
Section: Discussionmentioning
confidence: 92%
“…Also, Pandey (2018) found that thiamethoxam 25 WG was effective against aphids, leaf hopper and, whitefly. Maurya et al (2015) found that Thiamethoxam 70% WS as tomato seed treatment protected tomato from aphid and thrips with significant increase in the fruit yield. Abdelatef et al (2022) found that both spray ultra-low volume (ULV) and low volume (LV) techniques with thiamethoxam reduced Whitefly B. tabaci infestation and significantly increased cucumber fruit quality yield.…”
Section: Residues and Dissipation Of Thiamethoxam In Tomato Leaves An...mentioning
confidence: 92%